Diethyl ether adducts of trivalent lanthanide iodides. Issue 23 (10th May 2019) - Gompa, Thaige P.; Rice, Natalie T.; Russo, Dominic R.; Aguirre Quintana, Luis M.; Yik, Brandon J.; Bacsa, John; La Pierre, Henry S.
Abstract : The synthesis and structural characterization of molecular complexes of lanthanide iodides supported by the weak-base, diethyl ether, are reported. Abstract : The synthesis and structural characterization of the first molecular complexes of lanthanide iodides supported by the weak-base, diethyl ether, are reported. Single-crystal diffraction studies reveal a conserved [LnI3 ( mer -Et2 O)3 ] structure (Ln = Ce, Pr, Nd, Sm, Gd, Tb, and Tm). These precursors are prepared from lanthanide metal and iodine in diethyl ether for all lanthanides La to Tm (excluding Pm and Eu) and provide the THF adducts in good to excellent (60–91%) yield in a two-step process.